The Comparison of the Level of Aggressiveness of Oyama Karate and Mixed Martial Art Fighters - Łukasz Rydzik (Applied Sciences, 2022)
Background: Aggressive behavior is inherent in many sports, especially martial arts. It is usually considered undesirable; nevertheless, in some cases, it can be a motivating factor in a competition. It is important to distinguish types of aggression. The aim of this study was to compare the level of aggressiveness between athletes practicing mixed martial arts (MMA) and Oyama Karate. Methods: In total, 30 Oyama Karate and 30 mixed martial art athletes were asked about their aggressive behavior. The Buss–Perry Aggression Questionnaire was used in the study. Results were statistically analyzed. Results: There were statistically significant differences between the performance of Oyama Karate and MMA athletes (p < 0.001), which occurred in all the types of aggression tested (anger, physical aggression, hostility, and verbal aggression). Hence, the results of the study confirmed the accuracy of the research hypothesis that the level of intensity of aggression is higher in MMA fighters than in full-contact Oyama Karate fighters. Conclusions: Physical aggression was dominant in the evaluated fighters. The greatest difference between both groups of fighters was in verbal aggression, whereas the smallest was in hostility.